Eucommia ulmoides Oliver repairs the disorder of intestinal microflora caused by high starch in Micropterus salmoides and improves resistance to pathogens - Liu, Hongli; Li, Fulong; Tang, Hong; Chen, Baipeng; Geng, Yi; Chen, Defang; Ouyang, Ping; Li, Liangyu; Huang, Xiaoli (Frontiers in Microbiology, 2023)
Eucommia ulmoides Oliver (EuO) is a natural medicine that can improve the composition of intestinal flora in fish, but more experiments and data are needed to support whether it can effectively improve the changes of intestinal flora and intestinal damage caused by high starch. This study examined the changes in intestinal structure as well as intestinal flora before and after the addition of EuO to high-starch diets and analyzed the effects of such changes on immune and digestive functions. The results showed that EuO reduces mortality during Nocardia seriolae attack and can reduce starch-induced intestinal inflammation. Eucommia ulmoides Oliver supplementation was able to alter the changes of intestinal flora in fatty acid degradation, bacterial chemotaxis, porphyrin metabolism and flagella assembly caused by high starch. By analyzing the abundance and correlation of bacterial communities, three bacterial communities that were significantly related to the intervention effect of EuO were screened. Further analysis revealed that EuO supplementation reduced the increase in abundance of Limnochordaceae, Nitrolancea, Lysinibacillus, and Hydrogenispora induced by high starch, which were negatively correlated with levels of the immunoreactive substance LZM in fish. This study reveals the regulatory effects of EuO on the intestinal flora of Micropterus salmoides fed on high starch diets, and provides a theoretical basis for reducing starch damage to fish in production.